The Effect of Customer-Orientation Behavior of Malaysian Hotel Front Liners on Job Satisfaction and Organizational Commitment - Afif, Hamzan @ Shukri (2011)
Customer-orientation behavior which refers to the employee’s tendency or predisposition to meet client’s need in the job context, has become a prime variable of interest for organizations wishing to market and promote products to the customers. In hotel industry in particular, one way to improve the quality of services offered is through the prompt and courteous service quality given by the front liners that is by adopting customer-orientation behavior. Therefore, utilization of customer-orientation behavior has been aggressively promoted by hoteliers. However, a complete understanding of the consequences of customer-orientation behavior is presently lacking. This study explores the influence of customer-orientation behavior on job satisfaction, and organizational commitment. Hypothesized relationships are tested using survey responses from a sample of 68 hotel front liners. Results revealed a positive relationship between customer-orientation behavior and job satisfaction as well as organizational commitment of the front liners. Results are compared with earlier findings and implications for future research are discussed.